Cage‐Shaped Polymers Synthesis: A Comprehensive State‐of‐the‐Art. Issue 12 (26th December 2021) - Gauthier‐Jaques, Martin; Mutlu, Hatice; Theato, Patrick
Abstract: Researchers have dedicated their efforts for the creation of a wide choice of complex and precise macromolecular architectures over the past 100 years. Among them, cyclic polymers benefit from their absence of terminal chains and from their singular topology to minimize their hydrodynamic volume in solution, increase their chemical stability, limit their number of possible conformations as well as a reduce their propensity to crystallize or to form entanglements in comparison to their acyclic counterparts. While monocyclic structures have already been widely investigated and reviewed, reports on more complex polycyclic structures are rare. In this regard, cage‐shaped polymers—consisting of at least three polymer chains covalently interconnected through strictly two junction points—have received little attention over the past two decades. Although their synthesis is a worthy challenge, only a few synthetic methodologies of polymer cages were successfully developed so far. Thus, this review intends to highlight the key concepts of the conception of cage‐shaped polymers in addition to propose an actual and exhaustive state‐of‐art concept of their synthesis to rationally promote the next‐generation synthesis strategies. Abstract : Only a few methodologies for the synthesis of polymer cages were successfully developed so far. This review intends to highlight the key concepts of the conception of cage‐shaped polymers in addition to propose an actual and exhaustive state‐of‐art concept of their synthesis to rationally promote future developements in this field.